Review of the genus Scutylenchus Jairajpuri, 1971 (Nematoda: Tylenchida), with description of Scutylenchus dongtingensis n. sp. from rhizosphere soil of grass in China - Xu, Chun–Ling; Xie, Hui; Zhao, Chuan–Bo; Zhang, Song–Bai; Su, Xiu–Min (Zootaxa, 2012)
The genus Scutylenchus Jairajpuri 1971 (Nematoda: Tylenchida) is reviewed, and a compendium of the most importantdiagnostic characters with a key to the species are given. A new species, Scutylenchus dongtingensis n. sp., is describedfrom China, extracted from rhizosphere soil around grass near Dongting Lake in Hunan province. The new species ischaracterized by having body cuticle with 16–20 longitudinal striae forming blocks; lateral field with 6 incisures forming5 bands without areolation or any other decoration; a slightly offset head with 7 striae; slender stylet 22–25μm long, withcone about three fifths of stylet length; excretory pore inconspicuous under light microscope, located in region of anteriorpart of gland bulb in lateral view; female vulva slit transverse with small epiptygma in lateral view; conspicuous dot-likephasmid located at about one third of tail length posterior to anus; female tail subcylindrical, terminus round, annulated,terminal cuticle thickened; spicule slender, well developed, 27–32μm long, usually not protruded from cloaca;gubernaculum crescent-shaped, may be protruded from cloaca; bursa conspicuous, extending over tail terminus in ventral view.